Himawari House - Becker, Harmony (New York, NY : First Second, 2021)
"When Nao returns to Tokyo to reconnect with her Japanese heritage, she books a yearlong stay at the Himawari sharehouse. There she meets Hyejung and Tina, two other girls who came to Japan to freely forge their own paths. The trio live together, share meals, and even attend the same Japanese-language school, which results in them becoming fast friends. But will they be able to hold one another up as life tests them with new loves, old heart breaks, and the everyday challenges of being fish out of water?"--Provided by publisher.
Keywords: Japanese Americans -- Comic books, strips, etc; Young women -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Shared housing -- Comic books, strips, etc -- Japan; Student exchange programs -- Comic books, strips, etc; Japanese Americans -- Fiction; Young women -- Fiction; Friendship -- Fiction; Shared housing -- Fiction -- Japan; Student exchange programs -- Fiction; Cartoons and comics; Tokyo (Japan) -- Comic books, strips, etc; Tokyo (Japan) -- Fiction; Comics (Graphic works); Graphic novels